Prevalence of congenital cryptorchidism in Estonia. (12th November 2021) - Kübarsepp, Viljo; Varik, Karin; Varendi, Heili; Antson, Anne; Veinla, Maie; Nellis, Georgi; Merila, Mirjam; Salundi, Urve; Astover, Valve; Punab, Margus
Abstract: Background: Cryptorchidism is one of the most common urogenital malformations. Cryptorchidism prevalence varies greatly in different countries and populations. The aim of the current study was to determine and analyse cryptorchidism prevalence in Estonia. Materials and methods: During 2012–2015, all consecutively born 5014 boys at Tartu University Hospital were examined for cryptorchidism. All the subjects with cryptorchidism were followed up for at least 6 months to assess spontaneous testicular descent. Results: Note that 2.1% cases had one or both testicles undescended at birth, 1.6% cases at expected date of birth, 1% cases at 3 months of age, and 0.8% cases at the age of 6 months had cryptorchidism. Cryptorchidism prevalence at birth was higher in preterm boys (11.9%), boys of low birth weight (16.7%) and boys small for gestational age (14%) but was lower in full‐term newborn boys (1.1%). During follow‐up, testes descended spontaneously in 61.6% of boys, more commonly in prematurely born boys (92%) and boys with low gestational weight (93%) as compared to full‐term cryptorchid boys (29.2%) and cryptorchid boys with normal birth weight (34%). At the age of 6 months, cryptorchidism prevalence was equalized in preterm boys (0.9%) and boys with low birth weight (1%) as compared to full‐term boys (0.7%) and boys with normal birth weight (0.7%). Boys SGA required surgical intervention more commonly than boys with normal birth weight. Ethnically, cryptorchidism prevalence at birth was similar among Estonians and non‐Estonians. Conclusion: Our data revealed that cryptorchidism prevalence, especially in full‐term boys, is lower in Estonia than reported in the other Nordic‐Baltic countries and worldwide.